Productivity Antecedents of Brazilian Courts of Justice: Evidence from Justiça em Números - Alamir Costa Louro; Washington Romão Santos; Helio Zanquetto Filho (BAR: Brazilian Administration Review, 2017)
Public sector managers and researchers have emphasized the importance of performance measurement. Nevertheless, few theoretical and empirical studies are found in Brazilian Judiciary Courts’ literature. In order to empirically identify which variables (IT investments, own or outsourced human capital) are more relevant for improving productivity, the current research proposes a model using secondary data extracted from the Justiça em Números (Justice in Numbers) report, using structural equation modeling for the analysis. The results suggest that: (a) all variables are relevant for improving productivity in Brazilian Courts, confirming our first three theoretical hypotheses; and (b) own human capital has a greater impact on productivity than outsourced, confirming the fourth. For those who are responsible for reforms, this finding indicates that IT is not the most important investment. However a question remains: Seen as a cure for almost all problems in the public sector, is it possible to improve performance without hard IT investments? For future research there are some additional questions: Why is own human capital more relevant than outsourced? Which variables should be included in the model for improving the general significance? The answers can help improve Brazilian court productivity.